2005
DOI: 10.1590/s0036-36342005000200005
|View full text |Cite
|
Sign up to set email alerts
|

Distribución heterogénea de la prevalencia de anticuerpos contra Trypanosoma cruzi en donadores de sangre en Puebla, México

Abstract: T. cruzi seroprevalence distribution is heterogeneous, from 0% to 2.6%, with higher seroprevalences in the regions of Tehuacan-Sierra Negra and Mixteca.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 7 publications
0
0
2
Order By: Relevance
“…Overall, the HBsAg prevalence in blood donors was 0.066% throughout the studied period, which is below the range reported by most studies of blood donors during the last decade in several Mexican states: 0.23% (15), 0.30% (16), 0.20% (17), 0.18% (18), 0.057% (19), and 0.216% (20). In these studies, the presence of anti-HBc was not analyzed; however, the overall anti-HBc prevalence of 1.19% was lower than that found in two other studies of Mexican blood donors (4.42% (6) and 1.82% (7)) and almost one third of the 3.3% prevalence reported for Mexican adults with different socioeconomic status (4).…”
Section: Discussioncontrasting
confidence: 57%
“…Overall, the HBsAg prevalence in blood donors was 0.066% throughout the studied period, which is below the range reported by most studies of blood donors during the last decade in several Mexican states: 0.23% (15), 0.30% (16), 0.20% (17), 0.18% (18), 0.057% (19), and 0.216% (20). In these studies, the presence of anti-HBc was not analyzed; however, the overall anti-HBc prevalence of 1.19% was lower than that found in two other studies of Mexican blood donors (4.42% (6) and 1.82% (7)) and almost one third of the 3.3% prevalence reported for Mexican adults with different socioeconomic status (4).…”
Section: Discussioncontrasting
confidence: 57%
“…The prevalence found in this study is lower than that reported by the ENSE in the 80´s when the prevalence of seropositivity for T. cruzi was 3.2% in Hidalgo (Monteón et al, 2005).…”
Section: Discussioncontrasting
confidence: 80%
“…The variable age has been found in studies developed in Brazil, Argentina, Bolivia, Colombia, Spain, Ecuador, Mexico, Peru, and Venezuela. For being a silent disease that reveals its symptoms only in 10 to 30 years after the protozoan infection [3], in most research, age is found in a directly proportional relation to the CD diagnosis, that is, older people have more probability of discovering the infection [31,53,101,115,[124][125][126][127][128][129][130].…”
Section: ➢ Agementioning
confidence: 99%